Analysis of the Application of Lean Maintenance to Optimize Transformer Maintenance Duration at MRO Company PT. Servo Indonesia Perkasa - Juma’in, Juma’in; Rosalendro Eddy Nugroho (International Journal of Education, Vocational and Social Science, 2024)
This study was conducted with the aim of identifying the causes of waste that cause delays in the completion of Maintenance, Repair and Overhaul Transformer work carried out by PT SIP, to determine recommendations and proposals for appropriate improvements to overcome waste during the implementation of Maintenance, Repair and Overhaul Transformer activities carried out by PT SIP, and to evaluate the implementation of lean maintenance to overcome waste that causes delays in the completion of Maintenance, Repair and Overhaul Transformer work carried out by PT SIP. The method used in this research is the Quantitative Descriptive method. The results showed that CSM Analysis at eight stages of Pre Shutdown to Energize activities identified waste such as delays in HSE approval, material mismatches, lack of labor skills, slow delivery of samples, and unavailability of adequate personal protective equipment. Proposed improvements include parallel work, moving manpower to other activities, ensuring the availability of tools and parts, and modifying delivery schedules and locations for temporary placement of parts to optimize the duration of the Inspection & Overhaul stage. The implementation of Lean Maintenance at PT SIP reduced the overhaul duration to 297 hours, improved labor effectiveness, ensured spare parts readiness, increased productivity through ISO 45001, and kept SOPs and Work Instructions (IK) complete and up-to-date, all of which contributed to OHS risk management and operational efficiency.